Opinion paper: effectiveness of sirolimus in treating partial Di George syndrome with autoimmune lymphoproliferative syndrome-like features - van der Werff ten Bosch, Jutte (Frontiers in Pediatrics, 2023)
Di George syndrome is a disorder well known by pediatricians, caused by deletions in chromosome 22q11.2 and presenting with a wide range of clinical abnormalities, including immunodeficiency. Thymic function is diminished, leading to a decreased output of naive T cells (naïve T-helper cells, naïve T-regulatory cells, naïve cytotoxic T cells) as compared to healthy age matched controls. Immunedysregulation, such as autoimmunity and immunoproliferation are common in these patients, because the lack of a correctly functioning T cell repertoire. treatment of these complication are a challenge in many immunodeficiencies, including Di George syndrome. Gu et al discuss a case of a patient with 22q11 deletion and lymphoproliferation and treated successfully with Sirolimus. This opinion paper highlights the need to collect information on the treatment of patients with immunoproliferation through sharing of information of individual cases and international cooperation.